Effect of grinding process of steam-rolled barley grain on plasma glucose and leucine kinetics and protein synthesis in sheep. Issue 1 (1st January 2018) - Sano, Hiroaki; Saito, Yuko; Al-Mamun, Mohammad
ABSTRACT: An isotope dilution method of [U- 13 C]glucose and [l- 13 C]leucine was simultaneously conducted to determine the effect of grinding process of steam-rolled barley grain on rates of plasma glucose and leucine turnover and whole-body protein synthesis (WBPS) in sheep. Six adult sheep were assigned to two dietary treatments and the experiment utilized a crossover design for two 21-day periods. The experimental diet was consisted of mixed hay and steam-rolled barley grain (1:1 ratio). Barley grain was treated either with or without grinding (GR diet and SR diet, respectively). Sheep were fed isoenergetically and isonitrogenously in both the treatments. The primed-continuous infusion method of [U- 13 C]glucose and [1- 13 C]leucine was simultaneously performed on day 21. The pH and ammonia concentrations in rumen fluid decreased ( P < 0.05) and concentrations of total VFA, acetate, propionate and n-butyrate increased ( P < 0.05) after feeding. Rates of plasma glucose and leucine turnover and WBPS did not differ between the dietary treatments. It is likely that grinding process of steam-rolled barley grain did not influence plasma glucose and leucine kinetics and WBPS in sheep fed the diets of mixed hay and barley grain at 1:1 ratio.